PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR - Zumrotun Lutfiah; Antik Estika Hader; Yuyun Windiyani (STKIP Subang, 2024)
This research aims to determine the effect of using the Make A Match Type Cooperative learning model in class 1 Pancasila Education subjects. This is motivated by the low learning outcomes in Pancasila Education learning. This research is experimental research that uses a pre-experimental research design, with a pre-Experimental Design type of One Group Pretest-Posttest Design research. The location of this research was SDN 12 Koto Baru, Koto Baru District, Dharmasraya Regency. The research sample consisted of 21 students who were all class I students. The data collection instrument used was a 10-item multiple choice test, which had been tested for validity and reliability. The research results showed that the average pretest score was 65.71 and the average posttest score was 81.90. Description of research data from pretest-posttest data analysis, using the Wilcoxon test shows a significance value of 0.001 < 0.05. Which means there is an influence in implementing the Make A Match type cooperative learning model in class 1 of SDN 12 Koto Baru.